High-Growth Firms Rising Tide Lifts All Boats - de Nicola, Francesca (The World Bank, 2018)
How do high-growth firms affect the rest of the economy? This paper explores this question using Hungarian administrative microdata. It finds evidence of stronger productivity growth for firms supplying and operating in industries with more high-growth firms. The surge of high-growth firms' demand for intermediate inputs could explain this positive vertical spillover. Firms with intermediate productivity levels seem most likely to benefit from this effect. The results hold irrespective of the level of spatial aggregation